The Status of Water and Sanitation Facilities in Public Primary Schools in Oyo State, Nigeria: Progress toward Achieving the SDG 6 - Oluwaseun Addie (Environmental Health Insights)
Water and sanitation facilities in schools are directly linked to the attainment of Sustainable Development Goal (SDG) 6; however, these facilities are often grossly inadequate in both quality and quantity in public primary schools (PPS) in developing countries. This study examined the existing water and sanitation facilities in PPS in Oyo State, Nigeria, to identify disparities. Using ANOVA, variables extracted from the 2020 Oyo State Annual School Census report were analyzed and mapped to reveal spatial distribution at the local government level. Five water sources and 4 types of sanitation facilities were identified. Significant variations were observed across local government types (urban, semi-urban & rural, and rural) with respect to enrollment ( P  = .000), total number of toilets ( P  = .033), PPS with wells ( P  = .002), PPS with no water source ( P  = .001), PPS with flush toilets ( P  = .001), and PPS with other toilet types ( P  = .011). With sanitation facility availability below 20%, open defecation is likely to be prevalent in these schools. For the well-being of the pupils and the entire population of the state, the government needs to prioritize the provision of potable drinking water and improved sanitation facilities in PPS, while considering the need for facilities to be gender sensitive.